Prosthesis Embodiment in Lower Extremity Limb Loss: A Narrative Review - Tuyet Thao Nguyen; Bingjie Wang; Haddy Alas; Quincy Jones; Chase Clark; Sabrina Lazar; Shaddy Malik; Joshua Graham; Yasmeen Talaat; Chris Shin; Jonathon Schofield; Toran Macleod; et al. (Applied Sciences)
Lower limb prosthesis abandonment is a significant challenge, leading to reliance on walking aids, such as wheelchairs, which frequently do not match the patient’s needs and lead to increased morbidity. Prosthesis abandonment is driven by a lack of embodiment, the latter defined as the integration of a prosthetic device into one’s body schema. This review evaluates interventions enhancing embodiment through three dimensions: ownership, agency, and co-location. The aim of this narrative review is to ask what interventions are available to improve embodiment, and what dimensions of embodiment should be included in the standard of care for lower-limb amputation surgery and componentry development. This narrative is constructed through a thorough literature search on how the aforementioned dimensions of embodiment can be optimized. In the studies reviewed, standardization of embodiment metrics and longitudinal data are lacking, hindering clinical translation. Future work must prioritize patient-centered design, integrate multidimensional assessments, and address practical issues to expand eligibility for advanced interventions.